Livelihood Perspective: Determinants Of Micro Business Sustainability After Covid-19 In Payakumbuh West Sumatera - Sufiawan, Nur Ari (Politeknik Negeri Bengkalis, 2023)
This article aims to study how business capital, product innovation, social media, micro-business financing, ability to make financial reports and business length affect micro businesses' sustainability in Payakumbuh. Primary data was obtained from questionnaires distributed to one hundred micro-entrepreneurs in five sub-districts in Payakumbuh. This data was obtained using multiple linear data analysis methods. According to the authors, micro-business sustainability in Payakumbuh is positively and significantly influenced by factors such as venture capital, social media, micro-business financing, and business length. On the other hand, the authors find that product innovation and the ability to create financial reports do not have a partial impact.